La planificación operativa y su relación con el control de gestión en la Municipalidad Distrital de Sanagorán, Provincia de Sánchez Carrión, año 2017 - Ramírez Llaury, Elena Benilda (2018)
The objective of this research was to demonstrate the direct and determining relationship between Operational Planning and Management Control in the District Municipality of Sanagorán, Province of Sánchez Carrión, year 2017. The respective research problem was: What is the relationship between Operational Planning and the Control of Management in the District Municipality of Sanagorán, Province of Sánchez Carrión, year 2017?. This study was developed under the transactional descriptive design of the correlational type; its population consisted of 04 managers and 20 heads of the District Municipality of Sanagorán, constituting at the same time in the sample. For data collection, the survey technique was used, whose instrument was the questionnaire. After analyzing the respective results, the hypothesis that establishes that there is a direct and conditioning relationship between Operational Planning and Management Control in the District Municipality of Sanagorán, Province of Sánchez Carrión, year 2017, was established. The main conclusion is that Operational Planning and Management Control in the District Municipality of Sanagorán have a direct and determining relationship, as has been demonstrated by means of the Pearson Correlation Coefficient, where r = 0.752 has been obtained; In addition, both variables qualify at a high level. He also recommended that the improvements that should lead to strengthening the operational planning to improve the management control of the District Municipality of Sanagorán, should be emphasized in the strategic framework and the definition of goals, since they are being developed to a lesser extent.